2011
DOI: 10.1111/j.1755-3768.2011.02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Transretinal uveal melanoma biopsy with 25‐gauge vitrectomy system

Abstract: ABSTRACT.Purpose: To evaluate the efficacy and the safety of uveal melanoma transretinal biopsy using 25-gauge vitrectomy system. Methods: At the patient's request of a tissue diagnosis, nine posterior uveal melanomas treated by proton-beam therapy were biopsied during the insertion of tantalium markers. Results: The diagnosis was uveal melanoma, confirmed in all cases using cytological (7 of 9) and histological analysis (2 of 9). Immunocytochemistry was performed on all samples (9 of 9). In eight of nine pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Our finding is comparable to frequencies reported by other case series of vitreous cutter biopsies ranging from 72.2% to 88.9% (Abi‐Ayad et al. ; Grewal et al. ; Nagiel et al.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding is comparable to frequencies reported by other case series of vitreous cutter biopsies ranging from 72.2% to 88.9% (Abi‐Ayad et al. ; Grewal et al. ; Nagiel et al.…”
Section: Discussionsupporting
confidence: 91%
“…Five studies with a total of 35 patients have reported safety outcomes after PPV with transretinal biopsy in eyes with untreated melanoma. [21][22][23][24][25] After histopathologic confirmation of melanoma, these eyes underwent treatment with plaque radiotherapy (13 eyes), enucleation (11 eyes), protonbeam irradiation (10 eyes), or transscleral resection (1 eye). No cases of intraocular melanoma dissemination, extrascleral extension of melanoma, or local melanoma recurrence were detected.…”
Section: Commentmentioning
confidence: 99%
“…[3][4][5][6] Although performed under direct visualization, it is challenging to assess the vitreous cutter probe depth within the choroidal tumor and chorioretinal biopsy does confer a greater risk of iatrogenic morbidity including subretinal hemorrhage, vitreous hemorrhage, retinal detachment and the possibility of extrascleral extension. 4,[7][8][9][10][11][12][13][14] First described in 2010 by Oshima et al, and recently introduced commercially, the 27-gauge microincision vitrectomy system offers advantages compared to larger gauges in terms of smaller scleral wounds, decreased postoperative pain and inflammation, and faster visual recovery. 15 Although the efficacy of transvitreal retinochoroidal biopsy with a 25-gauge vitrector system has been demonstrated, no series regarding outcomes of 27-gauge vitrectomy assisted transvitreal choroidal or subretinal biopsy have been published since the commercial introduction of this technology by several different manufacturers.…”
Section: Introductionmentioning
confidence: 99%